Human vaginal microbiota colonization is regulated by female sex hormones in a mouse model - Rahman, Nuzhat; Mian, M. Firoz; Nazli, Aisha; Kaushic, Charu (Frontiers in Cellular and Infection Microbiology, 2023)
Clinically, a Lactobacillus rich vaginal microbiota (VMB) is considered optimal for reproductive outcomes, while a VMB populated by anaerobes is associated with dysbiosis and the clinical condition bacterial vaginosis (BV), which is linked to increased susceptibility to sexually transmitted infections and adverse reproductive outcomes. Mouse models that mimic eubiotic and dysbiotic VMB are currently lacking but could play a critical role in improving protective interventions. In this study, probiotic, eubiotic, and dysbiotic models were first developed in normal mice, using probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14, eubiotic Lactobacillus crispatus, or dysbiotic Gardnerella vaginalis strains. Following a single administration, L. rhamnosus and L. reuteri persisted in the mouse vaginal tract for up to eight days, L. crispatus persisted for up to three days, and G. vaginalis persisted for up to two days, as measured by quantitative plating assays and qPCR. Colonization of G. vaginalis was facilitated by the presence of mucin. Endogenous sex hormones were manipulated by either ovariectomizing (OVX) mice or administering 17β-estradiol and progesterone pellets in OVX mice. The lack of endogenous hormones in OVX mice dramatically decreased VMB bacterial load compared to normal mice. None of the exogenous bacteria including Lactobacilli could colonize OVX mice for more than 24 hours. Treatment with 17β-estradiol but not progesterone restored the endogenous microbiota and colonization with Lactobacilli and G. vaginalis. Interestingly, 17β-estradiol treated mice had significantly increased levels of glycogen, compared to OVX and progesterone-treated mice. These results suggest there is a dynamic interaction between sex hormones and the VMB, which can affect bacterial diversity and the ability for a VMB to colonize.